2016
DOI: 10.1126/sciadv.1501691
|View full text |Cite
|
Sign up to set email alerts
|

Observation of image pair creation and annihilation from superluminal scattering sources

Abstract: Researchers experimentally investigate the superluminal kinematics of scattering light sources through ultrafast time-resolved imaging.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
3
23
0
1
Order By: Relevance
“…Furthermore, the set of photons cutting the paper towards the origin have a shorter travel time (t traverse is lesser) -from laser to paper -than the other set of photons cutting toward infinity. This type of superluminal pair splitting has been verified experimentally in another context 11 .…”
Section: B Starting Orientation: Beam Parallel To the Papersupporting
confidence: 60%
“…Furthermore, the set of photons cutting the paper towards the origin have a shorter travel time (t traverse is lesser) -from laser to paper -than the other set of photons cutting toward infinity. This type of superluminal pair splitting has been verified experimentally in another context 11 .…”
Section: B Starting Orientation: Beam Parallel To the Papersupporting
confidence: 60%
“…Although an example of RID has been recovered in the laboratory (Clerici et al 2016), its occurrence has not been clearly isolated, as yet, elsewhere. Previously, though, papers about IACT imaging have briefly indicated that such an effect could occur.…”
Section: Introductionmentioning
confidence: 98%
“…In physical problems of this nature, due to the difficulty (or impossibility) of observing the phenomenon itself, the use of simulations might be interesting, both in classical and quantum setups. Using classical means, processes such as superluminal motion [7] or the formation of an event horizon in a white hole [8] can be simulated. The use of quantum simulators has recently brought results in physical processes of difficult or dubious observation, such as the simulation of a traversable wormhole [9], space-times in which superluminal trips are allowed and even CTCs [10], Hawking radiation [11], magnetic monopoles [12] or tachyonic particles [13].…”
Section: Introductionmentioning
confidence: 99%